2021
DOI: 10.1088/1755-1315/807/2/022015
|View full text |Cite
|
Sign up to set email alerts
|

Farming schemes and characteristics of Kalibening Avocado in Kebondalem Village, Semarang Regency, Central Java

Abstract: One of the plants that have high economic prospects is the avocado plant. In addition to its various benefits, from fruit to leaves, avocado also has a high economic value and has the potential to be developed in Indonesia. One of the avocados that have good prospects is the Kalibening avocado in Kalibening Hamlet, Kebondalem Village, Jambu District, Semarang Regency, Central Java. This study aims to determine the characteristics and income level of Kalibening avocado farmers which is carried out using two far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Avocado peel has proven to be used as natural dyes of cotton fabric [15]. It was reported that avocado production in 2018 was 410,094 tonnes [16]. Avocado consists of pulp (65-72%), stone (20-21%) and peel (7-15%) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Avocado peel has proven to be used as natural dyes of cotton fabric [15]. It was reported that avocado production in 2018 was 410,094 tonnes [16]. Avocado consists of pulp (65-72%), stone (20-21%) and peel (7-15%) [17].…”
Section: Introductionmentioning
confidence: 99%